Civil Law Tradition and Access to Justice: A Comparative Legal Politics of Civil Procedure in Indonesia and South Africa - Muhammad Fadly Nasution; Jan Alizea Sybelle (PATTIMURA Legal Journal, 2026)
Introduction: This article analyzes the comparative civil law tradition and its influence on access to justice through the lens of the Politics of Civil Procedure Law in Indonesia and South Africa. Both countries have a deep colonial history that shapes their judicial structures and litigation procedures to this day. In Indonesia, the use of outdated colonial regulations creates barriers for justice seekers, while in South Africa, hybrid systems face the challenge of massive socio-economic inequality. Purposes of the Research: The purpose of this study is to evaluate the impact of the persistence of colonial inherited civil procedural law on access to justice and to analyze the political direction of civil procedure reform in both countries, particularly related to digitalization and integration of customary law in the modern legal system. Methods of the Research: This research uses normative legal research methods with a comparative approach, a statute approach, and a conceptual approach. Secondary legal materials are analyzed qualitatively to compare policy developments in Indonesia and South Africa. Results Main Findings of the Research: The findings show that Indonesia is still stuck in the HIR/RBg formalism that limits procedural protection, despite modernization efforts through e-Court. In contrast, South Africa has integrated the right of access to justice into the constitution, but faces obstacles on litigation costs. The legal politics of the two countries are now leading to unification and digitalization to overcome access inequality.